FREQUENCY OF PNEUMOTHORAX AMONG PATIENTS PRESENTED WITH LARGE VOLUME THORACENTESIS - NAEEM , OM; AHMAD , M; ABBASI , WZ; ZAMAN , MH; AHMAD , A; SHAMSHAD , S (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the frequency of pneumothorax among patients who underwent large-volume thoracentesis. A cross-sectional study was conducted at the Department of Pulmonology, Pak Red Crescent Medical College & Teaching Hospital, Lahore, from January 2023 to June 2023. The study included 110 patients, aged between 50 and 75 years, of both genders, who presented with a large volume of thoracentesis. The frequency of pneumothorax was determined. The mean age of the patients was 62.04±7.04 years, with male patients accounting for 62.7% and female patients accounting for 37.3%. The frequency of pneumothorax was found to be 13.6%. No significant statistical association was observed between pneumothorax and gender. The study found that the frequency of pneumothorax among patients who underwent large-volume thoracentesis was 13.6%.